Razlike v gibalnih sposobnostih med študentkami glede na status telesne teže - Matejek, Črtomir (Revija za elementarno izobraževanje, 2016)
The main aim of the research was to find out whether there are any differences in physical fitness between non-overweight, overweight and obese female students. Research was carried out on 178 female students from the Faculty of Education Maribor (aged 20.3 years, SD= 1.09). The students were classified as non-overweight, overweight, and obese according to age and sex specific body mass index (BMI) cut-off points. In order to assess their physical fitness, nine different tests that cover explosive leg power, repetitive trunk and upper extremities power, flexibility, balance, eye-hand coordination, agility, and endurance were used. ANOVA was used to assess the differences in physical fitness between non-overweight, overweight, and obese groups. Statistical significance was set at the a level of 0.05. Results show that 79.9 % of students were in the non-overweight group, 14.0 % in the overweight group, and 6.61 % in the obese group. The differences in all physical fitness tests, except in sit-and-reach test and sit-ups test, between non-overweight, overweight, and obese female students are statistically significant (p<0.05). We have established that the non-overweight female students achieved a higher level of physical fitness than their overweight and obese peers. In addition, overweight students achieved a higher level of physical fitness than obese students. These data suggest, that in the early adulthood population the level of physical fitness and weight status are closely related.
Keywords: gibalne sposobnosti; physical abilities; elementary education students; motorične sposobnosti; motor competences; študentke